Ionic Liquids: Design Parameters for Ionic Liquid–Molecular Solvent Blend Electrolytes to Enable Stable Li Metal Cycling Within Li–O2 Batteries (Adv. Funct. Mater. 27/2021). (2nd July 2021) - Neale, Alex R.; Sharpe, Ryan; Yeandel, Stephen R.; Yen, Chih‐Han; Luzyanin, Konstantin V.; Goddard, Pooja; Petrucco, Enrico A.; Hardwick, Laurence J.
Abstract : In article number 2010627, Alex R. Neale, Laurence J. Hardwick, and co‐workers present the stability enhancements at Li‐metal anodes for Li‐O2 cells using concentrated ternary electrolytes based on DMSO and an ionic liquid. Optimizing the critical DMSO–Li + solvation interactions protects the solvent at the Li metal interface, inhibiting corrosion reactions and dendritic deposition that occur in the presence of free DMSO, and improves the overall performance within Li‐O2 cells.